Examining Mathematics Achievement of Students from Different Provinces: What PISA 2018 says about Indonesia? - Kismiantini, Kismiantini; Setiawan, Ezra Putranda (SEAMEO Regional Centre for QITEP in Mathematics, 2024)
Despite participating in PISA for more than 10 years, Indonesian students' mathematics achievements still tend to be low. On the other hand, PISA 2018 shows that students in two provinces, namely (1) Special Region of Yogyakarta, and (2) Special Region of Capital City Jakarta, exhibit higher mathematics achievement than students from other provinces. This research aim is to examine factors affecting students' mathematics performance in these three regions. We carried out statistical multilevel analysis with a random effects model using R software. Based on this analysis, we find differences in factors that influence students' mathematics achievement from three provinces. Variables that significantly influence students’ mathematics achievement in the three regions are parent support, home support, students' mastery goals, and students' competition. The only variables that were significant outside Special Region of Yogyakarta and Special Region of Capital City Jakarta were students' beliefs and students' ESCS. In the three provinces, the variables growth mindset, gender, and father's education level did not affect students' mathematics achievement.